Oral Formulation of Angiotensin-(1-7) Promotes Therapeutic Actions in a Model of Eosinophilic and Neutrophilic Asthma - Magalhães, Giselle Santos; Gregório, Juliana Fabiana; Cançado Ribeiro, Arthur Tonani Pereira; Baroni, Isis Felippe; Vasconcellos, Ana Victoria de Oliveira; Nakashima, Gabriela Pansanato; Oliveira, Isabel Fusaro Aguiar; Matos, Natália Alves de; Castro, Thalles de Freitas; Bezerra, Frank Silva; Sinisterra, Ruben D.; Pinho, Vanessa; et al. (Frontiers in Pharmacology, 2021)
The presence of eosinophils and neutrophils in the lungs of asthmatic patients is associated with the severity of the disease and resistance to corticosteroids. Thus, defective resolution of eosinophilic and neutrophilic inflammation is importantly related to exacerbation of asthma. In this study, we investigated a therapeutic action of angiotensin-(1-7) [Ang-(1-7)] in a model of asthma induced by ovalbumin (OVA) and lipopolysaccharide (LPS). Balb-c mice were sensitized and challenged with OVA. Twenty-three hours after the last OVA challenge, experimental groups received LPS and, one and 7 h later, mice were treated with oral formulation of Ang-(1-7). On the next day, 45 hours after the last challenge with OVA, mice were subjected to a test of motor and exploratory behavior and 3h later, lung function was evaluated and bronchoalveolar lavage fluid (BALF) and lungs were collected. Motor and exploratory activities were lower in OVA+LPS challenged mice. Treatment with Ang-(1-7) improved these behaviors and normalized lung function, reduced eosinophil, neutrophil, myeloperoxidase (MPO), eosinophilic peroxidase (EPO) and ERK1/2 phosphorylation (p-ERK1/2) in the lungs. In addition, Ang-(1-7) decreased the deposition of mucus and extracellular matrix in airways. These results extended those of previous studies by demonstrating that oral administration of Ang-(1-7) at the peak of pulmonary inflammation can be valuable for the treatment of neutrophil and eosinophil mediated asthma. Therefore, these findings potentially provide a new drug to reverse the natural history of the disease, unlike the current standards-of-care that manage the disease symptoms at best.